PENGARUH MOTIVASI KERJA, KOMPETENSI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PT HEXING TECHNOLOGY - Indra Irawan; Darlius (Pasca Sarjana Universitas Satya Negara Indonesia, 2018)
The aims of the research is to knows and analysize the effect of motivation of work, competences and compensation on the performance of PT Hexing Technology’s employees. PT Hexing Technology is the company who manufacturing in Prepaid Electrical Meter Measurement that located in Karawang, West of Java with the total of the employees are 150 employees whereas 118 employees (84%) are emplyees in production department who will be population and sample in this research caused the sampling technic to take a sample is using Sensus Sampling Technic. Meanwhile the design of research is using Quantitative methode. To analyze the effect of the independent variable (motivation of work, competence and compensation) to dependent variable then used of Multiple Linear Regression to knows which the variable that most effected. The research result by using SPSS version 22 shows that the motivation is positifly effected to the employee’s performance is 29,8% which mean that when the motivation increasing then performance getting increase. The competence variable is not effected to the employee’s performance . The compensation is effected to the performance is 25,4% which mean that when the motivation increasing then performance getting increase. Motivation, competence and compensation is simultantly are effected to the employee’s performance around 23,4% which mean that employee’s performance is effected by another factor who is not researched. The result of this research to be able to a guidance for the other parties to improve the performance of the employee. For that need to attention on the motivation of work in the organization. Beside that, need to be done improvement as continuously by competences and compensation to tha all employees.